Annals of the University of Bucharest. 70 Years of Geography Series - Responsibility for the Generations of Geographers - FLORINA GRECU (Annals of the University of Bucharest: Geography Series)
The editorial activity, carried out in publishing houses or journals (scientific or/and literary, cultural), is subject to special rigor to the scientific content that has to be provided, on the one hand, and to the social, historical and economic conditions that are specific to the moment, on the other hand.